CRIMINOLOGICAL REVIEW OF THE CRIME OF MURDER OF A SAME-SEX PARTNER AGAINST THEIR PARTNER - Hasbi Agusta, Muhammad Alif (Inspiring Law Journal, 2024)
The existence of homosexuals in Indonesia in 2008 became This is in the public spotlight due to the emergence of cases one involving gay people is a murder case This was carried out by Very Igham Hermansyah alias Ryan against Hery Santoso, motivated by jealousy towards his victim Novel, who liked his gay partner. Ryan was proven to have killed and even mutilated Hery Santoso because he felt jealous and displeased with the victim who had a crush on Novel's same-sex partner. The purpose of this research is to determine the factors that cause sexual deviant behavior, to determine the causes of murder committed by same-sex couples, and to determine the criminological study of criminal acts of murder committed by same-sex couples.The research carried out is normative legal research with a normative juridical legal approach using secondary data which processes data from primary legal materials, secondary legal materials and tertiary legal materials. Based on the research results, it is understood that 1) The factors causing sexual deviant behavior are sexual behavior disorders, social and social factors, genetic factors, and media factors in displaying pornography. 2) The causes of murder committed by homosexual couples are divided into internal factors and external factors. 3) The criminological view of homosexual couples who commit the murder of their partners when linked to the factors causing why the couple was able to commit the murder of their partner, there are several factors, namely: the psychological factor of the perpetrator who actually experienced a mental disorder to carry out the murder, then the individual factor in the form of feeling jealousy and revenge because they feel hurt towards the victim, as well as economic factors where the perpetrator deliberately commits murder so that he can take and control all of the victim's property. This can be seen from one example of the murder case committed by Very Idam Henyansyah alias Ryan against Hery Santoso in decision Number: 1036/Pid.B/2008/PN.DPK